2011
DOI: 10.1002/jbt.20384
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration by activated microglia across a nanofiltration membrane

Abstract: Microglia have been implicated in the pathogenesis of several neurodegenerative diseases, but their precise role remains elusive. Although neuron loss in the presence of lipopolysaccharide-stimulated microglia has been well documented, a novel coculture paradigm was developed as a new approach to assess the diffusible, soluble mediators of neurodegeneration. Isolated microglia were plated on membrane inserts that were coated with a layer of cellulose acetate. The cellulose acetate-coated membranes have nanofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Moreover it has been demonstrated that nitric oxide caused neuronal death not only via NMDA receptors, but it could also act directly upon immature neurons, through a not fully defined mechanism [111]. Recently, Graber et al ., [112] further supported NO production as an important mediator in microglia-induced neuron death. Damaging actions of NO, mostly mediated by microglia activation, have been extensively considered in recent reviews [113, 114].…”
Section: Nitric Oxide In the Cross-talk Between Microglia And Neuronsmentioning
confidence: 94%
“…Moreover it has been demonstrated that nitric oxide caused neuronal death not only via NMDA receptors, but it could also act directly upon immature neurons, through a not fully defined mechanism [111]. Recently, Graber et al ., [112] further supported NO production as an important mediator in microglia-induced neuron death. Damaging actions of NO, mostly mediated by microglia activation, have been extensively considered in recent reviews [113, 114].…”
Section: Nitric Oxide In the Cross-talk Between Microglia And Neuronsmentioning
confidence: 94%
“…Moreover, excessive microglial production of NO induced by UCB in hippocampal slices (Silva et al, 2012) may lead to increased cell death. In fact, and in contrast to the “protective” effects exerted by microglia in preventing excessive glutamate, microglia additionally contribute to the generation of NO, an important mediator in microglia-induced neuron death (Golde et al, 2002; Graber et al, 2012). Generation of NO may derive from iNOS activation, which once activated produces moderate levels of NO chronically without any requirement for further activation (Brown, 2010), or from constitutive NOS, probably originating in the case of UCB an overproduction that may inhibit phagocytosis (Kopec and Carroll, 2000), as we observed following the 4 h of incubation (Silva et al, 2010).…”
Section: Microglia In the Process Of Bilirubin-induced Inflammationmentioning
confidence: 99%
“…Nitric oxide also participates in the interrelationships between neurons and gliacytes. It was shown that increased synthesis of NO by microglia can lead to damage of neurons (Graber et al, 2012 ). iNOS is responsible for synthesis of nitric oxide in microglia (Contestabile et al, 2012 ).…”
Section: Nitric Oxide In Pathogenesis Of Schizophreniamentioning
confidence: 99%